CAEP 2015 Academic Symposium: Recommendations for University Governance and Administration for Emergency Medicine. (May 2016) - Petrie, David; Chopra, Anil; Chochinov, Alecs; Artz, Jennifer D.; Schull, Michael; Tallon, John; Jones, Gordon; MacPhee, Shannon; Ackerman, Margaret; Stiell, Ian G.; Christenson, Jim
Abstract: Objective: 1) To identify the strengths and challenges of governance structures in academic emergency medicine (EM), and 2) to make recommendations on principles and approaches that may guide improvements. Methods: Over the course of 9 months, eight established EM leaders met by teleconference, reviewed the literature, and discussed their findings and experiences to arrive at recommendations on governance in academic units of EM. The results and recommendations were presented at the annual Canadian Association of Emergency Physicians (CAEP) Academic Symposium, where attendees provided feedback. The updated recommendations were subsequently distributed to the CAEP Academic Section for further input, and the final recommendations were decided by consensus. Results: The panel identified four governance areas of interest: 1) the elements of governance; 2) the relationships between emergency physicians and academic units of EM, and between the academic units of EM and faculty of medicine; 3) current status of governance in Canadian academic units of EM; and 4) essential elements of good governance. Six recommendations were developed around three themes, including 1) the importance of good governance; 2) the purposes of an academic unit of EM; and 3) essential elements for better governance for academic units of EM. Recommendations included identifying the importance of good governance, recognizing the need to adapt to the different models depending on the local environment; seeking full departmental status, provided it is mutually beneficial to EM and the faculty of medicine (and health authority); using a consultation service to learn from the experience of other academic units of EM; and establishing an annual forum for EM leaders. Conclusion: Although governance of academic EM is complex, there are ways to iteratively improve the mission of academic units of EM: providing exceptional patient care through research and education. Although there is no one-size-fits-all guide, there are practical recommended steps for academic units of EM to consider. RÉSUMÉ: Objectifs: 1) L'étude visait à cerner les forces et les faiblesses des structures de gouvernance dans les unités d'enseignement de la médecine d'urgence (MU) et 2) à formuler des recommandations sur les principes et les voies susceptibles de guider les améliorations. Méthode: Sur une période de 9 mois, huit chefs de file bien établis en MU ont tenu des réunions par téléconférence, ont examiné la documentation et ont discuté des résultats de la recherche et de leurs expériences pour en arriver à l'élaboration de recommandations sur la gouvernance des unités d'enseignement de la MU. Les résultats et les recommandations ont été présentés au cours du symposium annuel sur les affaires universitaires de l'Association canadienne des médecins d'urgence (ACMU), après quoi les participants ont fait part de leurs observations. Les recommandations ont été modifiées en conséquence, puis transmises à la section des affaires universitaires de l'ACMU pour la collecte d'autres observations. Enfin, les recommandations définitives ont été le fruit d'un consensus. Résultats: Le groupe a dégagé quatre grands champs d'intérêt relatifs à la gouvernance : 1) les éléments de la gouvernance; 2) les relations entre les médecins d'urgence et les unités d'enseignement de la MU, ainsi qu'entre ces unités et les facultés de médecine; 3) l'état actuel de la gouvernance des unités d'enseignement de la MU au Canada; et 4) les éléments essentiels d'une bonne gouvernance. L'exercice a donné lieu à la formulation de six recommandations articulées autour de trois thèmes, notamment : 1) l'importance d'une bonne gouvernance; 2) les buts visés par les unités d'enseignement de la MU; et 3) les éléments essentiels à une meilleure gouvernance de ces unités. Les recommandations portaient principalement sur l'importance d'une bonne gouvernance, aussi sur la nécessité d'adaptation aux différents modèles selon le milieu local; sur l'obtention du titre de département à part entière, pourvu que cette reconnaissance soit profitable aux unités d'enseignement de la MU et aux facultés de médecine (ainsi qu'aux autorités sanitaires); sur le recours à des services de consultation pour tirer des leçons de l'expérience d'autres unités d'enseignement de la MU et sur la tenue d'une rencontre annuelle des chefs de file en MU. Conclusion: Certes, la gouvernance des unités d'enseignement de la MU est complexe, mais il est possible d'améliorer par réitération la mission de ces unités, soit la prestation de soins exceptionnels aux patients par la recherche et par la formation. Bien qu'il n'existe pas de panacée, plusieurs voies pratiques, recommandées s'offrent aux unités d'enseignement de la MU.